Opportunities for the Prevention of Hypertension by Nutrition Correction - Tetiana Nehoda (Journal of Global Pharma Technology, 2020)
AbstractIntroduction. There is much evidence of a relationship between salt intake and blood pressure levels. Limiting sodium chloride consumption significantly lowers blood pressure. The purpose of this study was to study the effectiveness of lowering blood pressure while limiting salt intake in men and women with high and normal blood pressure.Materials and methods. An annual study was conducted, a prerequisite of which was the selection of 2 groups: survey and comparison. They were comparable in terms of gender, age, professional composition and number of participants. To carry out a dietary examination required limiting the salt in the cooking to 0,5 g per serving.Results and discussion. After one year of dietary intervention, a significant decrease in systolic (SBP) and diastolic blood pressure (DBP) was found in men and women in the intervention group (p < 0,05) compared to the control group, which showed a natural decrease in blood pressure, a significant decrease in blood pressure was observed during the study period (p < 0,05). In addition, there was a significant decrease in body weight in the intervention group compared with the control group.Conclusions. Reduced salt intake significantly reduced SBP and DBP in men and women with high blood pressure over a longer follow-up compared with the control group.